Dispositional mindfulness and mental health among Chinese college students during the COVID-19 lockdown: The mediating role of self-compassion and the moderating role of gender - Zhang, Dan; Shen, Jianbo (Frontiers in Psychology, 2023)
College students' mental health has been seriously impacted during the global COVID-19 lockdown. There is evidence that dispositional mindfulness has a protective effect on mental health. However, few studies have examined the relationship between dispositional mindfulness and mental health from a self-compassion perspective. Additionally, it is unclear under what conditions the dispositional mindfulness is associated with mental health during the COVID-19 lockdown. To fill this gap, the present study examined self-compassion as a possible mediating factor and gender as a possible moderating effect between the dispositional mindfulness and mental health. The sample included 1018 Chinese university students during the COVID-19 lockdown (M age = 20.12; SD age = 1.17) who had completed self-report questionnaires on dispositional mindfulness, self-compassion, and mental health. According to the findings of mediation analysis, self-compassion partially mediated the relationship between dispositional mindfulness and mental health. The moderating analysis also revealed that the moderating effects of dispositional mindfulness, self-compassion, and mental health were significant. The mental health of male college students was significantly better protected, and buffering effects of dispositional mindfulness and self-compassion on the mental health of male college students were significantly stronger than those of female college students. These findings advance our understanding of the process between dispositional mindfulness and mental health and offer practical guidance for improving college students’ mental health during the COVID-19 lockdown.